Ekonomiczne aspekty funkcjonowania rynku mediów - Zawadzki, Piotr (Economic Aspects of Media Market Functioning, 2008)
The article presents economic aspects of media market functioning as the crucial determinants for this market functioning. The author presents both the definition and the levels of media economics, as well as the specific nature of media market functioning with particular emphasis on the dual nature of a media product, which on one hand becomes the source of information and on the other is an instrument of advertisement. The article presents the functioning models of market structures and also other market elements which influence media companies' activities and facilitate their obtaining competitive advantage. The author presents press as the example of efficiently functioning market structure, having also defined its significance for an overall media market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 182-192